Labor Insertion of Italian Professionals in Valencia: Between Emerging and Traditional Professions - Ingellis, Anna Giulia; Esteban, Fernando Osvaldo (Professions and Professionalism, 2021)
This paper presents the first results of a case study of Italian professionals’ mobility to the city of Valencia (Spain), highlighting the heterogeneity of the labor insertion paths within and between groups of emerging and traditional professionals. A qualitative method was used: 25 in-depth interviews and a two-year observation in virtual and real communities were carried out. According to our analysis, the heterogeneity of the labor insertion itineraries, revealed by the migrants’ narratives, can be understood by taking account of the various combinations of social, economic, and cultural capital with which the Italian professionals were endowed.